Characterization of WRKY Gene Family in Whole-Genome and Exploration of Flowering Improvement Genes in Chrysanthemum lavandulifolium - Ayoub Khan, Muhammad; Dongru, Kang; Yifei, Wu; Ying, Wang; Penghui, Ai; Zicheng, Wang (Frontiers in Plant Science, 2022)
Chrysanthemum is a well-known ornamental plant with numerous uses. WRKY is a large family of transcription factors known for a variety of functions ranging from stress resistance to plant growth and development. Due to the limited research on the WRKY family in chrysanthemums, we examined them for the first time in Chrysanthemum lavandulifolium. A total of 138 ClWRKY genes were identified, which were classified into three groups. Group III in C. lavandulifolium contains 53 members, which is larger than group III of Arabidopsis. The number of introns varied from one to nine in the ClWRKY gene family. The “WRKYGQK” motif is conserved in 118 members, while other members showed slight variations. AuR and GRE responsive cis-acting elements were located in the promoter region of WRKY members, which are important for plant development and flowering induction. In addition, the W box was present in most genes; the recognition site for the WRKY gene may play a role in autoregulation and cross-regulation. The expression of the most variable 19 genes in terms of different parameters was observed at different stages. Among them, 10 genes were selected due to the presence of CpG islands, while nine genes were selected based on their close association with important Arabidopsis genes related to floral traits. ClWRKY36 and ClWRKY45 exhibit differential expression at flowering stages in the capitulum, while methylation is detected in three genes, including ClWRKY31, ClWRKY100, and ClWRKY129. Our results provide a basis for further exploration of WRKY members to find their functions in plant growth and development, especially in flowering traits.